Creativity in the regular classroom: perceptions of gifted and non-gifted students - Gonçalves, Fernanda do Carmo (2013)
This study aimed to compare the perception of gifted and non-gifted students with respect to the climate for creativity in the classroom, in the disciplines of Mathematics and Portuguese Language, and to investigate the relationship between creativity and perception of classroom climate for creativity. Twenty-one gifted and 27 non-gifted 6th grade students who attended a public school in Brazil participated in the study. The gifted students evaluated teacher’s support to the students’ expression of ideas in Mathematics in a more satisfactory way compared to non-gifted, and they also showed greater interest in learning Mathematics in comparison to Portuguese Language. A positive correlation between creativity and perception of classroom climate was found for gifted students, and negative correlation for non-gifted students.